Unraveling Stage-Dependent Expression Patterns of Circular RNAs and Their Related ceRNA Modulation in Ovine Postnatal Testis Development - Li, Taotao; Luo, Ruirui; Wang, Xia; Wang, Huihui; Zhao, Xingxu; Guo, Yunxia; Jiang, Haitao; Ma, Youji (Frontiers in Cell and Developmental Biology, 2021)
Circular RNAs (circRNAs) have been shown to function in the reproductive systems including testis. However, their expression, as well as function in testicular development of sheep remain undefined. Herein, we performed RNA sequencing to reveal circRNA temporal expression patterns in testes of Tibetan sheep from different stages of maturation (3M, 3-month-old; 1Y, 1-year-old; 3Y, 3-year-old). A total of 3982, 414, and 4060 differentially expressed (DE) circRNAs were uncovered from 3M vs 1Y, 1Y vs 3Y, and 3M vs 3Y, respectively. Functional enrichment assessment indicated that the source genes of DE circRNAs were primarily engaged in spermatogenesis and testicular immune privilege including blood-testis barrier. We subsequently constructed the core circRNA-miRNA-mRNA interaction network for genes related to testicular function, such as spermatogenesis, germ cell development, blood-testis barrier, and cell cycle/meiosis. Furthermore, we validated the target associations between either circ_024949, circ_026259 or IGF1 and oar-miR-29b in this network, and revealed their similar expression signatures in developmental testes that they were extensively expressed in germ cells, Leydig cells and Sertoli cells, thus suggesting their broad functions in the functional maintenance of Leydig cells and Sertoli cells, as well as the development and maturation of male germ cells. Meanwhile, circ_026259 was shown to promote IGF1 expression through inhibition of oar-miR-29b in sheep Sertoli cells. This work gives the first global view for the expression and regulation of circRNAs in sheep testis, which will be helpful for providing new insights into the molecular mechanism of ovine testis function.